Antifungal, anti-biofilm, and anti-hyphal properties of N-substituted phthalimide derivatives against Candida species - Shaik, Shamshe; Lee, Jin-Hyung; Kim, Yong-Guy; Lee, Jintae (Frontiers in Cellular and Infection Microbiology, 2024)
Candida species comprise a ubiquitous pathogenic fungal genus responsible for causing candidiasis. They are one of the primary causatives of several mucosal and systemic infections in humans and can survive in various environments. In this study, we investigated the antifungal, anti-biofilm, and anti-hyphal effects of six N-substituted phthalimides against three Candida species. Of the derivatives, N-butylphthalimide (NBP) was the most potent, with a minimum inhibitory concentration (MIC) of 100 µg/ml and which dose-dependently inhibited biofilm at sub-inhibitory concentrations (10–50 µg/ml) in both the fluconazole-resistant and fluconazole-sensitive Candida albicans and Candida parapsilosis. NBP also effectively inhibited biofilm formation in other pathogens including uropathogenic Escherichia coli, Staphylococcus epidermidis, Staphylococcus aureus, and Vibrio parahaemolyticus, along with the polymicrobial biofilms of S. epidermidis and C. albicans. NBP markedly inhibited the hyphal formation and cell aggregation of C. albicans and altered its colony morphology in a dose-dependent manner. Gene expression analysis showed that NBP significantly downregulated the expression of important hyphal- and biofilm-associated genes, i.e., ECE1, HWP1, and UME6, upon treatment. NBP also exhibited mild toxicity at concentrations ranging from 2 to 20 µg/ml in a nematode model. Therefore, this study suggests that NBP has anti-biofilm and antifungal potential against various Candida strains.